The Effect of Product Quality, Service Quality, and Price on Purchase Decision at Lumos Agro Karya - Wicaksana, Arya Yodha; Hani, Rifki (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study aims to analyze the effect of product quality, service quality, and price on the purchase decisions of business partners at Lumos Agro Karya, a company in Malang’s food ingredient supply industry. Background Problems: The food ingredient supply industry for the Horeca sector has experienced significant growth in recent years, leading to increasingly high levels of competition. Research Methods: The research uses a quantitative method with a non-probability sampling technique (purposive sampling). Instrument testing included validity, reliability, linearity, heteroscedasticity, and multicollinearity tests. Hypothesis testing was conducted using the T-test, with all data analysis performed using SPSS version 25.00. Finding/Results:The results show that product quality, price, and distribution accuracy influence the purchasing decisions of business partners. Conclusion: The conclusion show that product quality, price, and distribution accuracy are significant determinants for business partners’ purchase decisions at Lumos Agro Karya.